Can Cephalopods Vomit? Hypothesis Based on a Review of Circumstantial Evidence and Preliminary Experimental Observations - Sykes, António V.; Almansa, Eduardo; Ponte, Giovanna; Cooke, Gavan M.; Andrews, Paul L. R. (Frontiers in Physiology, 2020)
In representative species of all vertebrate classes, the oral ejection of upper digestive tract contents by vomiting or regurgitation is used to void food contaminated with toxins or containing indigestible material not voidable in the faeces. Vomiting or regurgitation has been reported in a number of invertebrate marine species (Exaiptasia diaphana, Cancer productus and Pleurobranchaea californica) prompting consideration of whether cephalopods have this capability. This “hypothesis and theory” paper reviews four lines of supporting evidence: 1) The mollusc P. californica sharing some digestive tract morphological and innervation similarities with Octopus vulgaris is able to vomit or regurgitate with the mechanisms well characterised, and providing an example of motor programme switching; 2) A rationale for vomiting or regurgitation in cephalopods based upon the potential requirement to void indigestible material which may cause damage and ejection of toxin contaminated food; 3) Anecdotal reports (including from the literature) of vomiting- or regurgitation-like behaviour in several species of cephalopod (Sepia officinalis, Sepioteuthis sepiodea, Octopus vulgaris and Enteroctopus dofleini); 4) Anatomical and physiological studies indicating that ejection of gastric/crop contents via the buccal cavity is a theoretical possibility by retroperistalsis in the upper digestive tract (oesophagus, crop, stomach). We have not identified any publications refuting our hypothesis so a balanced review is not possible. Overall, the evidence presented is circumstantial so experiments adapting current methodology (e.g., research community survey, in vitro studies of motility, analysis of indigestible gut contents and faeces) are described to obtain additional evidence to either support or refute our hypothesis. We recognise the possibility that further research may not support the hypothesis therefore we consider how cephalopods may protect themselves against ingestion of toxic food by external chemodetection prior to ingestion and digestive gland detoxification post-ingestion. Reviewing the evidence for the hypothesis has identified a number of gaps in knowledge of the anatomy (e.g. the presence of sphincters) and physiology (e.g. the fate of indigestible food residues, pH of digestive secretions, sensory innervation, digestive gland detoxification mechanisms) of the digestive tract as well as a paucity of recent studies on the role of epithelial chemoreceptors in prey identification and food intake.